Revisión literaria y análisis del impacto en el desempeño organizacional al aplicar lean healthcare en los últimos 10 años (2021)
This document aims to conduct a literary review and analysis of the performance impact of organizations in implementing Lean healthcare techniques and philosophies. The development of this work is based on the results of an information collection through a bibliometric analysis of scientific and academic publications of the last ten years. Based on the results of that review, a collection of 100 duly filtered articles is made between the time lapse described above, for review. Based on the above, it is possible to know the appropriate tools of Lean for the processes of the health sector, highlighting the contributions that each of these has provided to the various departments and procedures. Likewise, the results of this project, help to give an insight into the application of the Lean in health care service providers, involving it, its critical success factors and barriers when adopting such methodologies as an alternative to improve organizational efficiencies.